Strongly coupled critical current density values achieved in Y1Ba2Cu3O7−δ coated conductors with near-single-crystal texture - Foltyn, S. R.; Arendt, P. N.; Jia, Q. X.; Wang, H.; MacManus-Driscoll, J. L.; Kreiskott, S.; DePaula, R. F.; Stan, L.; Groves, J. R.; Dowden, P. C. (Applied physics letters, 2003)
One of the most intensely researched subjects in the development of YBa2Cu3O7−δ (YBCO)-based coated conductors is the methodology for achieving ever-sharper film texture on flexible metal substrates. This is a critical issue due to the intrinsic weak-link behavior that results in depressed critical current density (Jc) in polycrystalline YBCO. Using ion-beam-assisted deposition of magnesium oxide, we have achieved YBCO texture on superalloy substrates approaching that on single-crystal oxide substrates. This advance has allowed us to fabricate coated conductor samples with Jcs that are as high as for films on oxide crystals; for example, >2 MA/cm2 (75 K, self-field) at a YBCO thickness of ∼1.5 μm.